The Effects of an ad Hoc Stability Training Protocol on Improving Balance in Young Volleyball Players - Pogoni, Juna; Ceruso, Rosario; Kaçurri, Arben; Peluso Cassese, Francesco; Esposito, Giovanni (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to evaluate the effectiveness of a customized training regimen in enhancing balance among young volleyball athletes. Materials and Methods. A total of 48 athletes (aged 14-16) from four volleyball teams participated, divided into Experimental (EG) and Control Groups (CG). Over six months, the EG adhered to a specialized protocol integrating balance exercises into warm-ups and post-training sessions, encompassing both static and dynamic exercises, while the CG followed a standard program. Balance assessments were conducted using the Leonardo Platform, with tests administered before and after implementing the protocol. Statistical analysis involved paired-samples and independent-samples T-tests to compare within-group changes and between-group differences. Results. The results obtained revealed significant improvements in the EG, particularly evident in the TanEC test (P = .00001), indicating enhanced stability without visual reference. Marked advancements were also noted in single-limb stability tests (1L_EO, P = .0018; 1L_EC, P = .0258). Conversely, the TanEO test showed no substantial group differences (P = .107), suggesting minimal impact on stability under visual conditions. Conclusions. These findings underscore the efficacy of tailored balance training in enhancing postural stability, motor coordination, and control among young volleyball players, advocating for the integration of targeted exercises in athletic training programs to optimize performance outcomes.